Safety and efficacy of the ChAdOx1 nCoV-19 vaccine (AZD1222) against SARS-CoV-2: An interim analysis of four randomised controlled trials in Brazil, South Africa, and the UK - Voysey, M; Clemens, SAC; Madhi, SA; Weckx, LY; Folegatti, PM; Aley, PK; Angus, B; Baillie, VL; Barnabas, SL; Bhorat, QE; Bibi, S; Briner, C; et al. (Elsevier, 2020)
Background: A safe and efficacious vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), if deployed with high coverage, could contribute to the control of the COVID-19 pandemic. We evaluated the safety and efficacy of the ChAdOx1 nCoV-19 vaccine in a pooled interim analysis of four trials.